2011
DOI: 10.1007/s00726-011-1068-y
|View full text |Cite
|
Sign up to set email alerts
|

Glycine and its N-methylated analogues cause pH-dependent membrane damage to enterotoxigenic Escherichia coli

Abstract: The current study first investigates the emulsifying potential of glycine and its N-methylated derivatives N-methylglycine (sarcosine), N,N-dimethylglycine (DMG) and N,N,N-trimethylglycine (betaine) under varying pH conditions. Subsequently, the effect of these test compounds on the membrane integrity of enterotoxigenic Escherichia coli (ETEC) was evaluated. Oil in water emulsions containing each compound show that DMG is a more potent enhancer of emulsification than glycine, sarcosine and betaine under the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 42 publications
4
15
0
Order By: Relevance
“…Cools et al (2010) found an improvement of crude fat, CP, and nitrogen-free extract apparent digestibility when 500 mg of DMG-Na/ kg of feed was supplemented in sow diets. This beneficial effect confirms the hypothesis that DMG acts as an emulsifying agent, as recently proven by Vanhauteghem et al (2012).…”
Section: Introductionsupporting
confidence: 76%
“…Cools et al (2010) found an improvement of crude fat, CP, and nitrogen-free extract apparent digestibility when 500 mg of DMG-Na/ kg of feed was supplemented in sow diets. This beneficial effect confirms the hypothesis that DMG acts as an emulsifying agent, as recently proven by Vanhauteghem et al (2012).…”
Section: Introductionsupporting
confidence: 76%
“…As previously shown for stationary phase ETEC [1], flow cytometric analysis of membrane integrity of log phase ETEC with SYTO 9/PI dual staining revealed a unique fluorescence pattern, directly related to the degree of membrane damage. Three bacterial subpopulations could thus be identified: membrane-intact live bacteria (A), membrane-damaged “intermediates” (B) and dead bacteria (C).…”
Section: Resultssupporting
confidence: 75%
“…All compounds were stored to manufacturers' guidelines until use. Compound characteristics are described by Vanhauteghem et al [1].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations